The impact of pension insurance types on the health of older adults in China: a study based on the 2018 CHARLS data - Yang, Dongliang; Ren, Zhichao; Zheng, Ge (Frontiers in Public Health, 2023)
Introduction Pension insurance is an essential safeguard for the quality of life and health of older adults because it provides a stable and dependable source of income after retirement. China has constructed a multi-level social security system to accommodate the diverse needs of older adults, and offers various levels of pension insurance to maximize their interests. Methods This study uses propensity score matching and ordinary least squares techniques to analyze 7,359 data from the 2018 China Health and Retirement Longitudinal Study (CHARLS) in order to explore the relationship between different pension insurance categories and the health of older individuals. Results The research findings reveal that advanced insurances greatly benefit the health of older adults more than basic pension insurances, and the findings pass the robustness test. In addition, the effect was found to be heterogeneous, depending on the location of retirement and the marital status of older adults.Our findings suggest that both material and non-material consumption may be potential mechanisms by which pension insurance affects the health of older adults, providing new evidence for the causal mechanism between pension insurance and the health of older adults. Discussion This study expands the scope of research on the health effects of pension insurance by covering a large representative sample across the country. The results show the important impact of the level of pension insurance on the health of older adults and can contribute to the development of social policies to promote the physical and mental health of older adults.